A sub-national hunger index for Ethiopia: Assessing progress in region-level outcomes - Schmidt, Emily; Dorosh, Paul A. (International Food Policy Research Institute, 2009)
Access to sufficient food and nutrients is essential for household welfare, as well as for accomplishing other development objectives. Households with insufficient access to food often face other challenges related to food insecurity including poor health and declines in productivity. In order to better target food aid assistance, evaluate progress, and design efficient intervention strategies, a transparent and reliable database on food insecurity is necessary. With the goal of providing a more straight-forward and standardized approach for calculating food insecurity, IFPRI developed a Global Hunger Index (GHI) in 2006 that allowed for easy comparison across countries. Recognizing the various dimensions of food insecurity, the GHI equally weights the proportion of people who are food energy deficient, the prevalence of underweight children under the age of five, and the mortality rate among children less than five years of age. Because national averages can mask important regional differences, we calculate a Sub-National Hunger Index for Ethiopia using data from 1999-2000 and 2004-05 (the latter year being the latest for which nationally representative household surveys are available). Our findings indicate that between 1999-2000 and 2004-05, there were substantial improvements in all components of the Hunger Index in all analyzed administrative regions of Ethiopia. There were also major improvements in both urban and rural areas, with a decline in the index from 47.6 to 29.9 in small urban areas (areas defined urban in the household survey with exception to Addis Ababa, Dire Dawa, and Harari) and from 43.6 to 32.6 in rural areas. Given rapid agriculture-led economic growth between 2004-05 and 2008-09, it is expected that when new household survey data is available, these indices will show continued improvement.